GOVERNMENT ACCOUNTING STANDARD, HUMAN CAPACITY, INTERNAL CONTROL SYSTEM AND FINANCIAL SUPERVISION AS A QUALITY ANALYSIS OF GOVERNMENT FINANCIAL STATEMENTS - Osmad Muthaher (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
This study aims to analyze how much the commitment of local government officials is to support the quality of financial reports through the use of information technology (e-reporting use) to support the success of the Semarang city government in obtaining Unqualified Opinion (WTP). Based on the results of the BPK audit the last five years showed that the Semarang city government experienced significant growth. Even Semarang city government is the only local government that has been able to apply accrual accounting bases in Central Java Province. The population in this study were all Regional Work Units (SKPD) in the Semarang City government as many as 50 SKPD. Samples were obtained using purposive sampling method. The sample obtained by 75 respondents from 15 SKPD in Semarang City Government for the analysis unit is the Head of SKPD and the Head of Finance & Accounting Section at the SKPD. To analyze and identify hypotheses, multiple regression analysis is used to determine the effect between variables. Based on the results of multiple regression tests, the results show that the variables of Financial Accounting Standards, HR Capability, Internal Control Systems and Regional Financial Supervision have a significant positive effect on the quality of financial report performance, while moderating variables namely Organizational Commitment have no significant effect on the quality of financial statements